Recombinant Tumor Necrosis Factor Receptor p75 Fusion Protein (TNFR:Fc) Alters Endotoxin-Induced Activation of the Kinin, Fibrinolytic, and Coagulation Systems in Normal Humans - DeLa Cadena, Raul A.; Majluf-Cruz, Abraham; Stadnicki, Antoni; Tropea, Margaret; Reda, Debra; Agosti, Jan M.; Colman, Robert W.; Suffredini, Anthony F. (Thrombosis and Haemostasis, 1998)
The effects of inhibition of tumor necrosis factor (TNF) on cell and protease activation were evaluated in 18 normal volunteers given endotoxin (4 ng/kg, iv) after an infusion of low (10 mg/m2 iv, n = 6) or high dose (60 mg/m2 iv, n = 6) recombinant human dimeric TNF receptor protein (TNFR:Fc) or its vehicle (placebo n = 6). Activation of the coagulation system occurred by 2 h in the TNFR:Fc vehicle-placebo group manifested by decreased prekallikrein functional levels and increased levels of prothrombin F1+2 fragments (p <0.0001). High or low dose TNFR:Fc delayed the fall in prekallikrein functional levels by 1 h and 4 h, respectively (p <0.0002), but did not inhibit the increase in circulating levels of prothrombin F1+2 fragments. In contrast, endothelium activation, characterized by increased levels of tissue plasminogen activator, plasminogen activator inhibitor-1, and von Willebrand Factor antigen was blunted by both low and high dose TNFR:Fc (p <0.001). While the endotoxin-associated decrease in platelet number was not altered, platelet-derived β-thromboglobulin peak levels were blunted and delayed by TNFR:Fc (p <0.02). Increased levels of neutrophil elastase were attenuated by low and high dose TNFR:Fc (p <0.001). These results suggest that although TNF is functionally linked to the activation of endothelium, neutrophils, coagulation, and fibrinolysis, alternative pathways are present in vivo that result in activation of the kallikrein-kinin system after endotoxin-induced TNF release. These alternative pathways may limit some of the anti-inflammatory effects of TNFR:Fc.